2012
DOI: 10.1177/0095244312448260
|View full text |Cite
|
Sign up to set email alerts
|

Role of vinyl thiethoxy silane grafted onto fluororubber in compatibilization of fluororubber and silicone rubber blends

Abstract: The blends of fluororubber (FKM) and silicone rubber (MVQ) were prepared by the incorporation of fumed silica using vinyl thiethoxy silane (VTEO) grafted onto FKM (FKM-g-VTEO) as a compatibilizer. The effect of the compatibilizer loading on the curing characteristics, mechanical properties, heat aging properties and oil resistance was investigated. Dynamic mechanical analysis indicates that FKM-g-VTEO acts as a compatibilizer in the FKM/MVQ blends. The tensile properties and oil resistance of FKM/ MVQ blends i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[14][15][16][17][18][19][20] Due to the presence of hydrogen bonds in uoroelastomers, only minor changes in conformational mobility and steric hindrance of C-F hand, and hence, their performances at low temperature are unsatisfactory. 21 Moreover, quite a few studies have focused on the blend modication of uoroelastomers, [21][22][23][24][25][26][27] so some functional uoropolymer compatibilizers [28][29][30][31] should be explored to achieve compatibility 32 between uoroelastomers and other materials. The new functions and new curing chemistry of uoropolymer materials, as well as the compatibility technologies with conventional materials, can be categorized into the functionalization of uoroelastomers.…”
Section: Prof Yongping Bai Received His Phd Degree In Polymer Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20] Due to the presence of hydrogen bonds in uoroelastomers, only minor changes in conformational mobility and steric hindrance of C-F hand, and hence, their performances at low temperature are unsatisfactory. 21 Moreover, quite a few studies have focused on the blend modication of uoroelastomers, [21][22][23][24][25][26][27] so some functional uoropolymer compatibilizers [28][29][30][31] should be explored to achieve compatibility 32 between uoroelastomers and other materials. The new functions and new curing chemistry of uoropolymer materials, as well as the compatibility technologies with conventional materials, can be categorized into the functionalization of uoroelastomers.…”
Section: Prof Yongping Bai Received His Phd Degree In Polymer Materialsmentioning
confidence: 99%
“…Graing reaction is a signicant pathway to functionalize uoropolymers by hanging functional groups such as carboxyl, 80 hydroxyl, 53 sulphonic acid, 81 and carbonyl 52 onto their backbones. Many methods have been adopted to achieve a large variety of uoride gras, including chemical oxidation, 54,[82][83][84] free radical polymerization (FRP), 29,30 high-energy inducement (HE) 53 and several novel chemical modications. 85 Table 1 shows the utilized monomers and corresponding methods for functionalization of different uoropolymers.…”
Section: Functionalization Via Grafting Reactionmentioning
confidence: 99%
“…[ 26 ] The effect of FKM‐g‐vinyltriethoxysilane in the FKM/MVQ rubber blend as an effective compatibilizer has also been studied and the results showed that 9 phr loading of the compatibilizer enhances the mechanical, thermal properties and improves filler to rubber interactions. [ 27 ] Wang et al have studied the dynamically cured polyvinylidene fluoride (PVDF)/MVQ/FKM blend system with the partial replacement of MVQ with FKM. [ 28 ] It was interpreted that with an increase in FKM content, the mechanical properties have improved and the nucleation of the PVDF phase was enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Fluororubber (FKM) of various types is capable of satisfying such demands for the unique combinations of mechanical properties and excellent thermal, oil, and chemical resistances, which is used in many industrial applications such as gaskets, seals, and O-rings in the petrochemical, automotive, and food processing industries. However, the disadvantages of FKM are lack of low temperature resistance and not easy to process due to its high Mooney viscosity [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%